Considerations Upon the Effects of Covid-19 Pandemic on the Romanian Economic Environment - Diana-Elena Velica Cârciumărescu; Lucian Belascu; Alexandra Horobet (Studies in Business and Economics, 2022)
The modern economy has faced, over time, several economic crises. They have determined changes in the behaviour of economic agents and a natural evolution towards the current entrepreneurial environment, taking into account the structural, quantitative, and qualitative dynamics of economic activity, general economic development goals, and technological progress. Starting with the first half of year 2020, most of the world was marked by a completely different situation - the health crisis generated by the SARS Cov-2 virus, with powerful and immediate negative effects at the level of both developing economies and stronger countries. The measures imposed by the Romanian government for crisis management during the state of emergency and alert generated the restriction or even suspension of the activity of diverse economic sectors. Limiting the freedom of movement of the population has led to habits change and reorientation of the consumers towards online markets. The markets had a chain reaction that generated a decrease in production capacity within the manufacturing industry, automotive industry and related, interconnected activities. The main objective of the paper is to analyse how the pandemics affected different Romanian sectors and to identify appropriate tools for market correction and orientation, based on a quantitative and qualitative analysis with the use of preliminary data available on the National Institute of Statistics and Trade Register database. The analysis reveals the pandemic’s effect on national accounts, GDP components, and the short-term impact on companies.